Effect of Dl-3-n-Butylphthalide on olfaction in rotenone-induced Parkinson’s rats - Wang, Jiawei; Li, He; Wang, Canran; Li, Dayong; Zhang, Yong; Shen, Meichan; Xu, Xiangdong; Wu, Tong (Frontiers in Neurology, 2024)
Background Parkinson’s disease (PD) is the second most common neurodegenerative disease after Alzheimer’s disease. Olfactory dysfunction (OD) is an important nonmotor feature of PD. Dl-3-n-Butylphthalide (NBP) is a synthetic compound isolated from Apium graveolens seeds. The present study was conducted to investigate the effect of NBP on olfaction in rotenone-induced Parkinson’s rats to explore the mechanism and pathway of OD in PD. Methods The PD model was established using rotenone-induced SD rats, divided into blank control, model, and treatment groups. A sham group was also established, with 10 rats in each group. The treatment group was given NBP (1 mg/kg, 10 mg/kg, and 100 mg/kg, dissolved in soybean oil) intragastrically for 28 days. Meanwhile, the control group rats were given intra-gastrically soybean oil. After behavioral testing, all rats were executed, and brain tissue was obtained. Proteomics and Proteomic quantification techniques (prm) quantification were used to detect proteomic changes in rat brain tissues. Results Compared with the control group, the model group showed significant differences in behavioral tests, and this difference was reduced after treatment. Proteomics results showed that after treatment with high-dose NBP, there were 42 differentially expressed proteins compared with the model group. Additionally, the olfactory marker (P08523) showed a significant upregulation difference. We then selected 22 target proteins for PRM quantification and quantified 17 of them. Among them, the olfactory marker protein was at least twofold upregulated in the RTH group compared to the model group.